Learning Beyond the Classroom: Teachers’ Perspectives of the Extracurricular Activities in Learning English as a Foreign Language - Talal Amara (Journal of English as A Foreign Language Teaching and Research, 2021)
Abstract The current study investigated teachers’ perspectives of the use of extracurricular activities in EFL context. Data for the study were collected from 187 questionnaire respondents from Arabic speaking countries. The findings reveal that most of EFL teachers in study context use ECAs in their teaching of English. They also show that teachers not only use these activities to improve language proficiency but also to promote other language related skills. The findings also reveal some challenges in implementing ECAs such as time convenience, school workload, lack of funding, some social and cultural barriers, and students’ perception of these activities. Based on the findings, the researcher suggests further investigation into some other factors such as teachers’ readiness to implement these activities and the different types of activities that work best for the study context.